Croatian school libraries on Facebook: meeting the needs of young library users - Hebrang Grgić, Ivana (Array, 2013)
Purpose – Purpose of this paper is to examine presence of Croatian school libraries on Facebook by analysing quality and quantity of interactions. Design/methodology/approach – In the paper, literature about libraries on Facebook is reviewed and the need for new researches on the topic is explained. Quantitative and content analysis of all Croatian school libraries on Facebook is presented. Quantitative analysis includes: metrics, features, number of items in features, number of libraries’ and users’ activities (posts, likes, comments and shares). Content analysis includes analysis of information section and posts published in two-month period. Findings – Croatian school librarians know how to use Facebook on a basic level, but some are not educated enough to administer Facebook presences – they use wrong kind of presence, administer it without planning and sometimes publish inappropriate content. Users of Croatian school libraries rarely interact, mostly by liking library’s status and they wait for their libraries to encourage the interaction. Practical implications – This research can help school librarians to see what they have to do to improve or to implement their Facebook activities. The improvement should advance library service, both on Facebook and in real life. Originality/value – The paper confirms that Croatian school librarians are aware of the importance of social networking sites for communication with patrons. This is the first complete study of Croatian school libraries on Facebook and intends to be a basis for a longitudinal study of school libraries’ presence on social networking sites. The study could also be a starting point for similar analysis worldwide.